2013
DOI: 10.3389/fmicb.2012.00444
|View full text |Cite
|
Sign up to set email alerts
|

Same, same but different: symbiotic bacterial associations in GBR sponges

Abstract: Symbioses in marine sponges involve diverse consortia of microorganisms that contribute to the health and ecology of their hosts. The microbial communities of 13 taxonomically diverse Great Barrier Reef (GBR) sponge species were assessed by DGGE and 16S rRNA gene sequencing to determine intra and inter species variation in bacterial symbiont composition. Microbial profiling revealed communities that were largely conserved within different individuals of each species with intra species similarity ranging from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 64 publications
2
53
0
Order By: Relevance
“…Most studies have compared the microbial communities of sponges from the same geographical region or sea (Erwin et al 2012, Schmitt et al 2012, Webster et al 2013. A study of 13 GBR sponge species re vealed a high core microbiome within each species but a low microbiome shared between the species; a maximum of 5 sponge species shared OTUs, and 91% of the OTUs were species-specific (Webster et al 2013). In another study of 3 sympatric Mediterranean Ircinia sp., Erwin et al (2012) identified host species-specific OTUs, OTUs shared between the 2 most phylogenetically related species, and OTUs common to 2 species sharing the same cryptic habitat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have compared the microbial communities of sponges from the same geographical region or sea (Erwin et al 2012, Schmitt et al 2012, Webster et al 2013. A study of 13 GBR sponge species re vealed a high core microbiome within each species but a low microbiome shared between the species; a maximum of 5 sponge species shared OTUs, and 91% of the OTUs were species-specific (Webster et al 2013). In another study of 3 sympatric Mediterranean Ircinia sp., Erwin et al (2012) identified host species-specific OTUs, OTUs shared between the 2 most phylogenetically related species, and OTUs common to 2 species sharing the same cryptic habitat.…”
Section: Discussionmentioning
confidence: 99%
“…According to Shade & Handelsman (2012), an abundant microorganism that is shared among all samples within a given habitat must play a significant function in the community. Therefore, recognizing core microbiota (microbes that are common to 2 or more samples) in complex microbial habitats is the first step in understanding systems ecology (Shade & Handelsman 2012, Webster et al 2013. Most studies have compared the microbial communities of sponges from the same geographical region or sea (Erwin et al 2012, Schmitt et al 2012, Webster et al 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other major themes addressed are the specificity or the ubiquity of the sponge microbiome (Erwin et al 2012a, Alex et al 2013, Webster et al 2013b) and the sponge symbiotic metabolism (Hunting et al 2010, Thomas et al 2010a, Freeman et al 2013. Additionally, there are number of papers on spatiotemporal dynamics of associated microbial communities assessing bacterial and also archaeal biodiversity (Sacristán-Soriano et al 2011b, Bjork et al 2013, Hardoim and Costa 2014.…”
Section: Sponge Chemical Ecology and Microbial Ecologymentioning
confidence: 99%
“…In fact, several dozen papers have already assessed the specificity of these sponge-associated communities (e.g. Erwin et al 2012a, Alex et al 2013, Webster et al 2013b, while others have shown that some symbiotic microorganisms can play a role as producers of biologically active compounds (Penesyan et al 2009, Genta-Jouve and Thomas 2012, Indaningrat et al 2016). In addition, there is another aspect that must be taken into account when assessing symbiont diversity and variability: different methods might influence the microbial community recovered, as shown by .…”
Section: Sponge Chemical and Microbial Ecology: Past Present And Futurementioning
confidence: 99%